Pendidikan Karakter Peduli Lingkungan Dalam Proses Pembelajaran Di Sd Alam Harapan KitaKabupaten Klaten - Husnun, Ra'id Naufal; , Minsih, S.Ag., M.Pd (2017)
ABSTRACK This study aims to: 1) To describe the environmental awareness of character education in the learning process in elementary Nature Harapan Kita Klaten district; 2) To identify environmental awareness of character education in the learning process in elementary Nature Harapan Kita Klaten district; 3) Describe the solutions to overcome barriers to environmentally conscious character education in the learning process in elementary Nature Harapan Kita Klaten district. The research is a qualitative research design with phenomenology. The informants are principals, teachers and students. Data collection techniques used were observation, interviews, and documentation. The validity of research data using triangulation of sources and techniques. The results showed that in the implementation of environmental care character education in the learning process in elementary Nature Harapan Kita Klaten district consists of three stages, namely the integration of the value of environmental care in the planning of learning, learning implementation, and evaluation. Barriers inhibiting factors namely internal and external obstacles, such as: conditions of teachers and students, facilities are limited, attention to parents who are still less against her and the community are less supportive of the development of the character of environmental care in children. The solution in overcoming obstacles is to bring in experts or speakers, adding to the budget funds are used, the family briefed or socialization, and school to educate more people about character education environmental awareness in the learning process. Keywords: character building, environmental care.